Are There Cultural Differences in Parental Interest in Early Diagnosis and Genetic Risk Assessment for Autism Spectrum Disorder? - Amiet, Claire; Couchon, Elizabeth; Carr, Kelly; Carayol, Jerôme; Cohen, David (Frontiers in Pediatrics, 2014)
Background: There are many societal and cultural differences between healthcare systems and the use of genetic testing in the U.S. and France. These differences may affect the diagnostic process for Autism Spectrum Disorder (ASD) in each country and influence parental opinions regarding the use of genetic screening tools for ASD. Methods: Using an internet-based tool, a survey of parents with at least one child with ASD was conducted. A total of 162 participants from the U.S. completed an English version of the survey and 469 participants from France completed a French version of the survey. Respondents were mainly females (90%) and biological parents (94.3% in the U.S.; 97.2% in France). Results: The mean age of ASD diagnosis reported was not significantly different between France (57.5±38.4 months) and the U.S. (56.5±52.7 months) (p=0.82) despite significant difference in the average age at which a difference in development was first suspected (29.7 months (± 28.4) vs. 21.4 months (± 18.1), respectively, p=7.10-4). Only 27.8% of U.S. participants indicated that their child diagnosed with ASD had undergone diagnostic genetic testing, whereas 61.7% of the French participants indicated this was the case (p=2.7.10-12). In both countries, the majority of respondents (69.3% and 80% from France and the U.S., respectively) indicated high interest in the use of a genetic screening test for autism. Conclusions: Parents from France and the U.S. report a persistent delay between the initial suspicion of a difference in development and the diagnosis of ASD. Significantly fewer U.S. participants underwent genetic testing although this result should be regarded as exploratory given the limitations. The significance of these between country differences will be discussed.